Implementing Class Wide Peer Tutoring to Enhance Students' Mathematical Reasoning Ability in Understanding Absolute Value Equations and Inequalities - Ega Gradini; Firmansyah B; Septia Wahyuni; Meri Mailinda (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
This article aims to determine the effectiveness of Class Wide Peer Tutoring (CWPT) implementation to improve students' mathematical reasoning abilities. This research is experimental research with a mixed-method approach. The research sample was determined through cluster random sampling. Data were collected through mathematical reasoning tests arranged according to indicators of mathematical reasoning ability. Data were analyzed using inferential statistics with the stages of normality, homogeneity, and hypothesis testing. The result shows that the implementation of CWPT enhances students' mathematical reasoning on Equations and Inequalities of an Absolute Value. Mathematical reasoning test results show that the 10th grader score of mathematical reasoning is 76.75 (Good). The indicator of mathematical reasoning that is the most difficult for students to master is